2014
DOI: 10.1007/s10661-014-3628-6
|View full text |Cite
|
Sign up to set email alerts
|

Microbial contamination of dental unit waterlines and effect on quality of indoor air

Abstract: The microbiological quality in dental unit waterlines (DUWLs) is considered to be important because patients and dental staff with suppressed immune systems are regularly exposed to water and aerosols generated from dental units (DUs). Opportunistic pathogens like Pseudomonas, Legionella, Candida, and Aspergillus can be present in DUWLs, while during consultations, bioaerosols can be dispersed in the air, thus resulting in effects on microbiological quality of indoor air. This present study represents microbio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 53 publications
3
29
0
6
Order By: Relevance
“…The fact that the fungi levels were lower in both monitored rooms than outdoors may be attributable to frequent cleaning and the use of UV lamps for disinfection purposes at the end of the business day. The microbiological composition of dental bioaerosols corresponds to the results obtained by others (Szymańska, 2007;Kadaifciler and Cotuk, 2014). An assessment of the potential health impacts of aerosol and bioaerosol particles in a dental office should be the subject of extended studies which should also consider actions aiming at minimizing the potential health risk both for dental personnel and patients.…”
Section: Particulate Mattersupporting
confidence: 86%
See 1 more Smart Citation
“…The fact that the fungi levels were lower in both monitored rooms than outdoors may be attributable to frequent cleaning and the use of UV lamps for disinfection purposes at the end of the business day. The microbiological composition of dental bioaerosols corresponds to the results obtained by others (Szymańska, 2007;Kadaifciler and Cotuk, 2014). An assessment of the potential health impacts of aerosol and bioaerosol particles in a dental office should be the subject of extended studies which should also consider actions aiming at minimizing the potential health risk both for dental personnel and patients.…”
Section: Particulate Mattersupporting
confidence: 86%
“…The performed studies mainly concentrated on the infection risk of dental workers due to their frequent exposure to bioaerosols (Nejatidanesh et al, 2013;Kadaifciler and Cotuk, 2014). A direct relationship between bioaerosols produced during dental procedures and the respiratory system infections has been demonstrated (Harrell and Molinari, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…This biofilm was made up of Gram negative bacteria both rods and cocci, in an extracellular matrix and included at least one fungal and one amoeba species. The organisms detected and identified, via isolation and cultivation in pure culture, were comparable to previous reports on the diversity of culturable microorganisms isolated from clinical dental waterline systems biofilms communities (Tall et al 1995;Barbeau & Buhler 2001;15 Dillon et al 2014 a ;Kadaifciler & Cotuk 2014). The bacterial counts on the outlet water from the simulated waterlines demonstrated contamination had occurred by day two.…”
Section: Discussionsupporting
confidence: 85%
“…Seventeen studies analyzed the microbial composition of dental clinics [23-29, [67][68][69][70][71][72][73][74][75][76]. The studies cumulatively identified 38 types of micro-organisms by using culture techniques (see Table 3 for complete overview of micro-organisms identified and Table 4 for study characteristics in dental setting).…”
Section: Dental Environmentmentioning
confidence: 99%